2014
DOI: 10.1021/ef501169m
|View full text |Cite
|
Sign up to set email alerts
|

Demulsification of Oleic-Acid-Coated Magnetite Nanoparticles for Cyclohexane-in-Water Nanoemulsions

Abstract: Oleic acid (OA)-coated magnetite (Fe3O4) nanoparticles, denoted Fe3O4@OA, were synthesized by co-precipitation in the presence of varying contents of OA. The Fe3O4@OA nanoparticles were characterized by X-ray diffraction, transmission and scanning electron microscopies, Fourier transform infrared spectroscopy, thermogravimetric–differential thermogravimetric analyses, and vibrating sample magnetometry. Increasing the OA content during preparation resulted in an increase of the OA-coating amount (A O, in units … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
78
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(93 citation statements)
references
References 41 publications
14
78
0
1
Order By: Relevance
“…These values are also slighter higher than the theoretically estimated ones found for the cases of magnetic or non-magnetic stirring during ferrophase coating. The results of this experimental study are concordant with those reported by other authors [7,16] that yielded single layer oleic acid magnetic nanoparticle systems with 10 nm and respectively 12-14 nm size. The MNP suspension response to electromagnetic field with frequency from 100 Hz to 1MHz (Fig.…”
Section: Resultssupporting
confidence: 93%
“…These values are also slighter higher than the theoretically estimated ones found for the cases of magnetic or non-magnetic stirring during ferrophase coating. The results of this experimental study are concordant with those reported by other authors [7,16] that yielded single layer oleic acid magnetic nanoparticle systems with 10 nm and respectively 12-14 nm size. The MNP suspension response to electromagnetic field with frequency from 100 Hz to 1MHz (Fig.…”
Section: Resultssupporting
confidence: 93%
“…[12] Figures 4 shows the TGA curves of the OA-decorated MNPs samples. [15] As presented in Figure 4, all OA-decorated MNPs samples exhibited two prominent weight loss stages at temperature F I G U R E 3 Raman spectra of MNPs with different loading amount of OA F I G U R E 4 TGA curves of MNPs with different loading amount OA below 600°C. A slight weight loss at temperature below 100°C could be noticed for all of the tested OA-decorated MNPs samples.…”
Section: Raman Analysismentioning
confidence: 94%
“…The weight loss of MNPs at below 100°C was attributed to the water content. [15] According to Mahdavi, Ahmad, [16] synthesized MNPs were reduced from magnetite phase to iron (II) oxide (FeO) phase because Iron (II) oxide is thermodynamically stable at temperature above 570°C (Equation 1). For undecorated MNPs, a weight loss of 3.68% was observed at 100-600°C.…”
Section: Raman Analysismentioning
confidence: 99%
“…With the help from magnets placed under sample containers, the magnetic property of MT and the rate of demulsification were improved. MT was also recyclable and reusable after each demulsification process, reducing the cost of chemicals in practical applications in the petroleum industry . Furthermore, DE was studied by undertaking demulsification tests within and without the magnetic field emitted from outside magnets for all types of crude oils in the presence of 0.98, 0.99, and 1.01 ppm MT, respectively, at 38.2, 45.2, and 50.1 °C (optimum conditions of concentration and temperature).…”
Section: Resultsmentioning
confidence: 99%
“…During the test, the quality of the separated water is also estimated (e.g. clear, cloudy, or containing crude oil) …”
Section: Introductionmentioning
confidence: 98%